HER2 overexpression a major risk factor for recurrence in pT1a‐bN0M0 breast cancer: results from a French regional cohort. (10th January 2014) - Rouanet, Philippe; Roger, Pascal; Rousseau, Emilie; Thibault, Severine; Romieu, Gilles; Mathieu, Andre; Cretin, Jacques; Barneon, Gilbert; Granier, Mireille; Maran‐Gonzalez, Aurelie; Daures, Jean P.; Boissiere, Florence; et al.
Abstract The management of pT1a‐bN0M0 breast cancer remains an area of controversy. Data from 714 patients classified as having pT1a‐bN0M0 breast cancer and treated, from 1999 to 2004 in the Languedoc‐Roussillon France, were analyzed. The human epidermal growth factor receptor 2 (HER2) status analyses were centralized. The objective of this study was to describe the prognosis of pT1a‐bN0M0 breast cancer according to HER2 distribution and hormonal status. The median follow‐up was 6.4 years. Ten‐year overall survival was 94%. HER2 overexpression was observed in 6.1% of the patients. The 10‐year prognosis of patients with HER2‐positive tumors was worse than that of those with HER2‐negative (disease‐free survival 73% vs. 89%, P < 0.0001). Tumor size (T1a/T1b) was not a relevant prognostic factor. The co‐expression of HER2 with hormonal receptors (HR) was associated with high recurrence at 10 years. In both univariate and multivariate analyses, the most relevant prognostic factor for this population was HER2 amplification. In multivariate analysis, patients with HER2‐positive tumors had higher risk of mortality (HR, 3.89; 95% CI, 1.58–9.56). In pT1a‐bN0M0 breast cancers, HER2 amplification or overexpression is a risk factor for recurrence. In HER2‐positive breast cancers, HR expression is associated with a poor prognosis despite the hormone therapy. For this population, a personalized management may be required.